2015
DOI: 10.1186/s40661-015-0012-3
|View full text |Cite
|
Sign up to set email alerts
|

Willingness and acceptability of cervical cancer screening among women living with HIV/AIDS in Addis Ababa, Ethiopia: a cross sectional study

Abstract: BackgroundIn Ethiopia, cervical cancer (CC) ranks the 2nd most frequent cancer and the country had 27.19 million women at risk of developing the disease though only 0.6 % women age 18-69 years was screened every 3 years. Nearly a quarter (22.1 %) of southern Ethiopia HIV (Human Immunodeficiency Virus) infected Women were positive for precancerous cervical cancer. Doing regular screening can prevent the disease by around half (45 %) of the cases in age of 30s and three quarter (75 %) cases in 50s and 60s.In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
89
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(119 citation statements)
references
References 25 publications
21
89
5
Order By: Relevance
“…This finding is lower than a similar the study done in Addis Ababa among female ART attendants [16]. This could most probably be due to the participants’ exposure to information through health professionals while they undergo regular follow up for ART services.…”
Section: Discussioncontrasting
confidence: 67%
“…This finding is lower than a similar the study done in Addis Ababa among female ART attendants [16]. This could most probably be due to the participants’ exposure to information through health professionals while they undergo regular follow up for ART services.…”
Section: Discussioncontrasting
confidence: 67%
“…According to the findings of our study, only 23.5% of respondents were ever tested for CC in their life time, which is significantly higher compared with the study done in among patients living with HIV/AIDS in Addis Ababa, Ethiopia, where only 11.5% of women screened for CC [16]. The uptake of screening in our study is also higher compared with the study conducted in Nigeria (9.4%) [23].…”
Section: Discussioncontrasting
confidence: 36%
“…Single population proportion formula was used with the assumption of 95% confidence interval, 5% margin of error, the proportion (p) of cervical cancer screening in women living with HIV/AIDS (11%) [16] and 5% for possible nonresponse was taken to determine a final sample size of 317. A systematic random sampling technique was then applied to select participants until the final sample size was attained.…”
Section: Sampling and Recruitment Strategiesmentioning
confidence: 99%
“…In a facility-based study in the same city among women living with HIV, 62.7% was willing to screen for cervical cancer, and a quarter (24.8%) of them decided to be screened in the near future [15].…”
Section: Cervical Cancer Screening Acceptancementioning
confidence: 99%
“…Facility-based study in Ethiopia, Addis Ababa, among women living with HIV indicated that 97 (88.2%) participants believed as the disease is preventable, and 31.4% knew the availability of the screening procedures for the disease [15]. In the same city of the country, among reproductive health service clients, 478 (91.9%) and 222 (42.7%) women heard about cervical cancer and cervical cancer screening, respectively [16].…”
Section: Introductionmentioning
confidence: 99%